SISTEM INFORMASI DATA ALUMNI DI SMAN 1 BENGKULU SELATAN BERBASIS WEB - Arrahman Arrahman; Andi Lala (UNIVED Press, 2022)
ABSTRACT :This study time to design a Web-Based Alumni Data Information System needed at Sman 1 South Bengkulu. The data collection technique of study used questionnaire, interview and documentation. The document can be in the form of writing, pictures, or monumental works of someone. The system development of this study used the waterfall method. The collecting of alumni data was still classified as manual by using archives that is still difficult to update alumni data. Therefore, to facilitate information from alumni, a web-based alumni data information system was designed at State Senior High School 1 South Bengkulu by using Xampp, Mysql and PHP programming languages. The research location was at State Senior High School1 South Bengkulu. The results of the research show that the alumni data information system at State High School 1 South Bengkulu is easier to be found particularly about updating the alumni data information system of State Senior High School 1 South Bengkulu. Keywords: Web-Based System, Alumni Data, Waterfall, Information System.